Arsenic removal from drinking water by advanced filtration processes - Duarte, António A. L. Sampaio (2011)
All over the world the presence of arsenic in water sources for human consumption has been raising great concern in terms of public health since many epidemiologic studies confirm the potential carcinogenic effect of arsenic. Because arsenic removal is the most frequent option for safe drinking water, the development of more efficient and sustainable technologies is extremely important. Membrane separation processes are suitable for water treatment because they can provide an absolute barrier for bacteria and viruses, besides removing turbidity and colour. Their application is a promising technology in arsenic removal since it does not require the addition of chemical reagents nor the preliminary oxidation of arsenite required in conventional treatment options. However, since membrane technologies such as reverse osmosis can be a very expensive and unsustainable treatment option for small water supply systems, it becomes crucial that alternative methods are developed. This work presents a few conclusions based on a laboratorial study performed to evaluate the efficiency of arsenic removal using ultrafiltration, microfiltration and solar oxidation processes under different experimental conditions for relevant parameters. The results showed removal efficiencies higher than 90%.